Oral health in the Japan self-defense forces - a representative survey - Furuyama Chisako; Sur Shachi; Saito Yoko; John Mike T; Kudo Yuka; Tsukasaki Hiroaki; Baba Kazuyoshi (BMC, 2011)
Abstract Background The oral health of military populations is usually not very well characterized compared to civilian populations. The aim of this study was to investigate two physical oral health characteristics and one perceived oral health measure and their correlation in the Japan self-defense forces (JSDF). Methods Number of missing teeth, denture status, and OHRQoL as evaluated by the Japanese 14-item version of the Oral Health Impact Profile (OHIP-J14) as well as the correlation between these oral health measures was investigated in 911 personnel in the JSDF. Results Subjects did not have a substantial number of missing teeth and only 4% used removable dentures. The mean OHIP-J14 score was 4.6 ± 6.7 units. The magnitude of the correlation between the number of missing teeth with OHIP-J14 scores was small (r = 0.22, p < 0.001). Mean OHIP-J14 scores differed between subjects with and without dentures (8.6 and 4.4, p < 0.001). Conclusions Compared to Japanese civilian populations, personnel of the JSDF demonstrated good oral health. Two physical oral health characteristics were associated with perceived oral health.